Five years of newborn screening for Pompe, Mucopolysaccharidosis type I, Gaucher, and Fabry diseases in Oregon - Sarah Viall; Patrice Held (Molecular Genetics and Metabolism Reports)
In October 2018, the Oregon newborn screening program began screening for four lysosomal storage disorders (LSDs) Pompe, Mucopolysaccharidosis Type I (MPSI), Gaucher, and Fabry. The laboratory used two different methodologies, digital microfluidics and tandem mass spectrometry, to measure the four LSD enzyme activities. Accuracy and precision were improved and lower false positive rates were observed with use of the Revvity NeoLSD assay on the mass spectrometry platform, as compared to the Baebies digital microfluidics method. All newborn specimens with screen positive results were reflexed to a second-tier molecular assay to identify variants in the target gene. Over the first five years of screening, 139 cases were referred for confirmatory testing and clinical evaluation due to presence of pathogenic/likely pathogenic variant(s)or variant(s) of unknown significance. These identified newborns were evaluated at the Oregon Health & Science University (OHSU) metabolic clinic in Portland, Oregon. However, due to the COVID-19 pandemic, clinicians had to pivot from in-person to virtual visits and triage on acuity, which impacted the time to diagnosis. Of referred babies, 3 are currently receiving treatment for their detected LSD. Over 50 babies have an inconclusive or possible late onset diagnosis with uncertain timeline for development of symptoms.